ผลของแซนแทนกัมต่อการพัฒนาขนมครกแช่เยือกแข็งทดแทนด้วยแป้งข้าวกล้องสังข์หยด (EFFECT OF XANTHAN GUM IN THE DEVELOPMENT OF FROZEN KANOM KROK REPLACED WITH SANGYOD BROWN RICE FLOUR) - พันชูกลาง, ขนิษฐา; พันชูกลาง, อภิชาติ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2020)
งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาผลิตภัณฑ์ขนมครกแช่เยือกแข็งทดแทนแป้งข้าวกล้องสังข์หยด พบว่าข้าวกล้องสังข์หยดมีค่า L* a* และ b* เท่ากับ 72.17±0.38, 6.50±0.11 และ 11.30±0.07 ตามลำดับ ความสามารถในการดูดซับน้ำและความสามารถในการละลายน้ำมีค่าเท่ากับ 2.68±0.04 และ 0.24±0.06 ตามลำดับ และเมื่อทำการทดแทนแป้งข้าวกล้องสังข์หยดที่ระดับร้อยละ 0 2 4 และ 6 ของน้ำหนักแป้งข้าวเจ้า พบว่าส่วนหน้าและส่วนฐานขนมครกมีค่า L* ลดลง ส่วนค่า a* และ b* เพิ่มขึ้น (p<0.05) เมื่อระดับการทดแทนแป้งข้าวกล้องสังข์หยดเพิ่มขึ้น โดยขนมครกที่ทดแทนแป้งข้าวกล้องสังข์หยดที่ระดับร้อยละ 6 มีคะแนนความชอบด้านลักษณะปรากฏ สี กลิ่น กลิ่นรส เนื้อสัมผัส และความชอบโดยรวมมากที่สุด แล้วทำการศึกษาการปรับปรุงคุณภาพขนมครกแช่เยือกแข็งในระหว่างการเก็บรักษาแบบแช่เยือกแข็งโดยการเติมแซนแทนกัมที่ระดับร้อยละ 0 1 และ 2 ของน้ำหนักแป้งทั้งหมด พบว่าค่า L* a* และ b* ของหน้าขนมครกหลังปรุงสุกที่เติมและไม่เติมแซนแทนกัมมีค่าไม่แตกต่างกัน (p≥0.05) และมีแนวโน้มเพิ่มขึ้นเมื่อระยะเวลาในการเก็บรักษานานขึ้น ส่วนค่า L* a* และ b* ของส่วนฐานขนมครกที่เติมแซนแทนกัมมีค่ามากกว่าขนมครกที่ไม่เติมแซนแทนกัม และมีค่า L* เพิ่มขึ้นเล็กน้อยเมื่อระยะเวลาการแช่เยือกแข็งนานขึ้น นอกจากนี้พบว่าความชื้นของขนมครกที่เติมแซนแทนกัมมีค่าคงที่ที่ระยะเวลาการเก็บรักษา 14 วัน และลดลงอย่างรวดเร็วที่ระยะเวลาการเก็บรักษา 21 วัน โดยขนมครกที่เติมแซนแทนกัมมีคะแนนความชอบในทุกคุณลักษณะมากกว่าขนมครกที่เติมแซนแทนกัมและคะแนนความชอบไม่มีความแตกต่างกันที่ทุกระดับการเติมแซนแทนกัม คำสำคัญ: ขนมครก ขนมไทยแช่เยือกแข็ง แป้งข้าวสังข์หยด แซนแทนกัม The objective of this research was to develop the frozen Thai dessert “Kanom-krok” from rice flour replaced with Sangyod brown rice flour. The physical characteristic of Sangyod rice flour was determined. L*, a* and b* values of Sangyod rice flour were 72.17±0.38, 6.50±0.11 and 11.30±0.07, respectively. Water absorption and solubility index of Sangyod rice flour were 2.68±0.04 and 0.24±0.06, respectively. The characteristics of sample replaced with Sangyod rice flour at the level of 0, 2, 4 and 6 g/100 g of rice flour were investigated. The result indicated that L* (lightness) value of sample was significantly decreased (p<0.05) and a* and b* value were significantly increased (p<0.05) when increasing the Sangyod rice flour level. The sample replaced with 6% Sangyod rice flour showed the highest score in appearance, color, odor, flavor, texture and overall liking aspects. The suitable amount of xanthan gum to improve Kanom krok during frozen storage time was also investigated. Xanthan gum was added into the Kanom krok formula at the level of 0, 1 and 2 g/100 g of total flour. The L*, a* and b* values on the top of cooked Kanom krok with and without xanthan gum shown were not significantly different (p≥0.05). Both samples were tended to increase when increasing frozen storage time. The L*, a* and b* values on the bottom of cooked Kanom krok with xanthan gum were higher than the sample without xanthan gum and L* value slightly increased with increasing frozen storage time. The water content of the Kanom krok threated with xanthan gum were constant throughout the 14 days frozen storage time and dramatically decreased on 21 days frozen storage time. In addition, the sample treated with xanthan gum showed the highest overall preference scores of samples comparing without xanthan gum. However, there were no significantly differences among the level of xanthan gum Keywords: Kanom krok, Frozen thai dessert, Sangyod rice flour, Xanthan gum